Iterative operation point determination of an automotive turbocharger-derived micro gas turbine using manufacturer compressor maps and CFD-based turbine modeling - Niwat Suksam; Kasemsil Onthong; Songtam Laosuwan; Aung Htet Oo; Kittipass Wasinarom (Results in Engineering, 2026)
• An iterative framework resolves thermodynamic operating points in micro gas turbines • Compressor maps integrate CFD-based turbine characteristics to replace empirical matching • Turbine irreversibility is quantified via viscous dissipation and exhaust kinetic losses • The predicted operating envelope is experimentally validated under no-load conditions • A novel framework enables reliable compressor–turbine pairing in cycle simulations Microturbine power systems comprise a wide range of thermodynamic components, and the accuracy of system-level performance simulations strongly depends on reliable prediction of the coupled compressor–turbine operating characteristics. Unlike conventional approaches that rely on empirical matching between specific compressors and turbines, this study proposes a novel physics-based iterative method for determining steady-state operating points of automotive turbocharger–derived micro gas turbines. The method couples manufacturer-provided compressor performance maps with turbine characteristics obtained from computational fluid dynamics (CFD) simulations. Consistency in mass flow rate, pressure ratio, and rotational speed is enforced iteratively to predict steady-state thermodynamic parameters over a wide range of shaft speeds. The proposed methodology is demonstrated using a commercially available automotive turbocharger operating at shaft speeds between 80,000 and 170,000 rpm. CFD analysis provides insight into turbine irreversibilities, including viscous and kinetic energy losses. Experimental validation under self-sustained, no-load operating conditions shows good agreement with predicted results, with deviations of all major thermal parameters remaining below 6% at a representative pressure ratio of 2.5, thereby confirming the reliability of the proposed approach. Furthermore, the applicability of the predicted operating envelope to a recuperated micro gas turbine cycle is evaluated. The results indicate a peak thermal efficiency of approximately 19% at shaft speeds between 130,000 and 170,000 rpm and pressure ratios ranging from 2.0 to 2.94. Overall, the proposed operating-point determination method provides a practical, accurate, and reusable tool for performance assessment and design optimization of microturbine-based energy systems under various configurations.
Keywords: Turbomachinery Performance and Optimization; Combustion and flame dynamics; Bladed Disk Vibration Dynamics